2021
DOI: 10.1038/s41598-021-03242-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and central accumulation of delta-9-tetrahydrocannabinol (THC) and its bioactive metabolites are influenced by route of administration and sex in rats

Abstract: Up to a third of North Americans report using cannabis in the prior month, most commonly through inhalation. Animal models that reflect human consumption are critical to study the impact of cannabis on brain and behaviour. Most animal studies to date utilize injection of delta-9-tetrahydrocannabinol (THC; primary psychoactive component of cannabis). THC injections produce markedly different physiological and behavioural effects than inhalation, likely due to distinctive pharmacokinetics. The current study dire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 44 publications
(110 reference statements)
14
53
1
Order By: Relevance
“…In comparison, two human laboratory studies using vaporized cannabis resulted in a C max of 14 ng/ml THC (25 mg dose) 26 and 47 ng/ml THC (50 mg dose) 27 . Our ranges of THC levels in plasma are comparable to what has been shown after IP injection of low doses of THC 0.5-3 mg/kg (∼25-75 ng/ml) 28-30 , after passive THC vapor exposure (35-73 ng/ml) 17, 28, 31 , and in rats self-administering THC vapor puffs (∼10-40 ng/ml) 32, 33 . Blood levels of THC following vapor exposure peak rapidly, within 5-10 minutes after exposure 28, 31 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In comparison, two human laboratory studies using vaporized cannabis resulted in a C max of 14 ng/ml THC (25 mg dose) 26 and 47 ng/ml THC (50 mg dose) 27 . Our ranges of THC levels in plasma are comparable to what has been shown after IP injection of low doses of THC 0.5-3 mg/kg (∼25-75 ng/ml) 28-30 , after passive THC vapor exposure (35-73 ng/ml) 17, 28, 31 , and in rats self-administering THC vapor puffs (∼10-40 ng/ml) 32, 33 . Blood levels of THC following vapor exposure peak rapidly, within 5-10 minutes after exposure 28, 31 .…”
Section: Discussionsupporting
confidence: 86%
“…Our ranges of THC levels in plasma are comparable to what has been shown after IP injection of low doses of THC 0.5-3 mg/kg (∼25-75 ng/ml) 28-30 , after passive THC vapor exposure (35-73 ng/ml) 17, 28, 31 , and in rats self-administering THC vapor puffs (∼10-40 ng/ml) 32, 33 . Blood levels of THC following vapor exposure peak rapidly, within 5-10 minutes after exposure 28, 31 . Blood levels of the key THC metabolites 11-OH-THC and THC-COOH were relatively low 7-11 and 8-13 ng/ml, respectively, mirroring what has been shown previously with vapor exposure models 28 .…”
Section: Discussionsupporting
confidence: 86%
“…However, this finding is not consistent between studies. The sex differences we see in THC metabolite concentrations are however consistent with both rodent and human studies [35,[49][50][51][52], and imply that females metabolize THC at a faster rate than males, likely due to a sex difference in liver metabolic enzymes [53].…”
Section: Discussionsupporting
confidence: 85%
“…Our model consistently showed that THC vapour inhalation increases food intake in the first 60-minutes after exposure. This timeframe is in line with the pharmacokinetic profile of THC vapour inhalation when administered using our protocol, where peak blood THC concentrations are detected immediately after vapour exposure and brain THC concentrations are highest throughout the first 60minutes following vapour exposure [35]. In addition, the time course of our THC feeding effects are consistent with that of previous THC or cannabis vapour exposure studies [19,23].…”
Section: Discussionsupporting
confidence: 85%
“…However, due to the large increase in popularity of e-cigarette usage [ 98 , 99 ], vapor administration has recently become a heavily researched route of administration. Interestingly, an animal model concluded that vaporized inhalation resulted in higher levels of THC within the plasma and brain, while injections resulted in higher levels of 11-OH-THC [ 100 ]. Overall, further research should be done in the future in order to be able to mitigate the differences between THC concentrations in animal models and humans based on different routes of administration.…”
Section: δ9-tetrahydrocannabinol (Thc)mentioning
confidence: 99%